Policy Dynamics of Curriculum Reform: Stakeholder Perceptions and Challenges in Implementing 21st-Century Skills Curriculum - Dedi Gunawan Saputra; Nur Hasbi; Zohaib Hassan Sain (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
This study explores the policy dynamics surrounding the implementation of the 21st-century skills-based curriculum, focusing on the perceptions and challenges faced by stakeholders at various educational levels. Through semi-structured interviews with teachers, principals, and policymakers, along with policy document analysis, the research identifies a significant gap between national policy design and its practical implementation at the school level. The study reveals that while the national curriculum emphasizes critical competencies such as critical thinking, creativity, and collaboration, there is a disconnect between these objectives and their classroom application. The main challenges include limited resources, cultural resistance, and lack of support from regional governments. The findings emphasize the need for a more flexible, context-sensitive curriculum that can be adapted to local needs. The study also emphasizes the importance of ongoing professional development and strong leadership to facilitate the adoption of innovative teaching methods. To address these challenges, the study calls for a coordinated approach involving national, regional, and school-level authorities to ensure effective curriculum reform. The research contributes valuable insights into the complexities of curriculum implementation and offers recommendations to improve educational policies and practices aimed at equipping students with the necessary skills for the modern world.